The expected returns and valuations of private and public firms - Cooper, Ilan; Priestley, Richard (Journal of Financial Economics, 2016)
Characteristics play a similar role in describing returns in private firms as in public firms. This evidence suggests a causal effect of optimal investment underlying the role of characteristics, as private firms do not have stock prices to over- or under-react on. Common factor models largely describe the cross section of investment returns of both types of firms, suggesting that the common factors are likely aggregate risk factors. Finally, the cost of capital and firm valuations are similar across private and public firms.